Green Economics: Unveiling the Economic and Environmental Dynamics of Recycling Initiatives - Gelbiro, Kent Marlo Adayo; Campos, Karl P. (Journal of Islamic Economics and Business, 2024)
Recycling stands out as a widely embraced waste management strategy globally, exerting a transformative influence on resource preservation, pollution mitigation, and the curbing of landfill waste. This research seeks to enhance our comprehension of sustainable recycling methodologies by delving into economic dynamics, environmental considerations, technological progress, policy structures, and social factors within the realm of recycling endeavors. The objective is to furnish crucial insights for governmental bodies, corporations, and communities embarking on their sustainability journeys. A comprehensive exploration was conducted utilizing reputable academic databases such as Google Scholar, ScienceDirect, and ResearchGate. Rigorous quantitative analysis was employed to amalgamate the amassed data, scrutinizing trends, patterns, and the interplay between recycling and its repercussions across various domains, including economics, technology, and the environment. The findings pertaining to economic dynamics reveal a robust correlation between recycling initiatives and factors such as employment rates, compensation levels, and tax revenues. Notably, there are discernible inter-sectoral variations, with ferrous metals leading in terms of job creation, wages, and tax contributions. Advancements in technology present opportunities for waste reduction, efficient sorting, and the manufacturing of new products, all of which play a pivotal role in fostering environmentally conscious waste management practices. The study underscores the significance of well-defined policy and regulatory frameworks in the realm of recycling, with a specific focus on the situation in the Philippines.